2012
DOI: 10.3945/ajcn.111.030650
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between brown adipose tissue activation and white adipose tissue accumulation in successfully treated pediatric malignancy

Abstract: The activation of BAT in pediatric patients undergoing treatment of malignancy is associated with significantly less adipose accumulation. This trial was registered at clinicaltrials.gov as NCT01517581.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Recent studies have suggested evidence and biochemical links between BAT, WAT [35], and skeletal muscle recruitment and development [3638]. Because BAT regulates thermogenesis [39] and energy expenditure, elucidating BAT associations with adiposity and muscle tone can lead to promising strategies aimed at facilitating the recruitment of brown adipocytes and in the preventive treatment of obesity during early stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested evidence and biochemical links between BAT, WAT [35], and skeletal muscle recruitment and development [3638]. Because BAT regulates thermogenesis [39] and energy expenditure, elucidating BAT associations with adiposity and muscle tone can lead to promising strategies aimed at facilitating the recruitment of brown adipocytes and in the preventive treatment of obesity during early stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of BAT in children is also dependent on disease status, weight, body composition, and the degree of sexual development (4, 18, 27, 28). Although excessive calorie intake has also been suggested to stimulate BAT activity in mice, whether diet induces BAT activation and thermogenesis in humans is the subject of considerable discussion (29).…”
Section: Recent Advances In Pediatric Bat Researchmentioning
confidence: 99%
“…The activation of BAT in children has been shown to be related to changes in weight and adiposity (28). Pediatric cancer patients with no visualization of BAT at diagnoses, but with evidence of BAT activity at follow-up PET/CT studies gained significantly less weight and subcutaneous and visceral adiposity than those who remained without BAT activity when disease-free.…”
Section: Recent Advances In Pediatric Bat Researchmentioning
confidence: 99%
“…Therefore, it is possible that effects of early suboptimal nutrition to depress BAT activity in rodents could underlie increased risk of obesity observed in precocial species as well. In support of this idea, reduced BAT function in children is associated with increased obesity [135,136,137]. …”
Section: Introductionmentioning
confidence: 99%
“…The idea that increased fat deposition associated with catch-up growth [17,18] programs impaired BAT function is supported by the observation that malnourished toddlers that experience catch-up growth exhibit increased leptin and low FGF21 as compared to those who maintain a slow growth trajectory [156]. The early phase of BAT development is likely important, because failure to develop active BAT in children is correlated with increased BMI [135,136,137]. Thus, these observations are consistent with the hypothesis that increased fat deposition during rapid growth in infancy programs diminished BAT capacity and reduced ability to increase energy expenditure when confronted with a higher nutritional plane.…”
Section: Introductionmentioning
confidence: 99%